The Attitude of Non-Malays towards Malay and English Language and their Perception on Language of Choice (Malay or English) for Multi-racial Communication in Malaysia: A Study on Non-Malay Tertiary Students (UNITEN) - Mohd Amin, Noraziah; Azam Abdul Rahman, Noor (International Journal of Engineering and Technology, 2018)
The Sultan of Perak, Sultan Nazrin Muizzuddin Shah in his speech at â€œMajlis Anugerah Kecemerlangan Sekolah Menengah Jenis Kebangsaan Sam Tet 2017â€ mentioned that it is indeed awkward and ironic, if a person who is a citizen of Malaysia, with all the interests and privileges of a citizen, cannot understand, cannot speak, cannot write and cannot read in the national language of his country (Amarudin, 2017). Nevertheless, in 2006, there was 29.8% of the students of SJKCs and 47.7% of the students of SJKTs who failed to achieve the minimum level of mastery of Bahasa Malaysia (Penulisan) or Malay Language (Writing) paper in â€œUjian Penilaian Sekolah Rendahâ€ (UPSR) (Tan, 2010). Obviously, it is vital to collect some insights from non-Malays in Malaysia particularly the youth regarding their perceptions towards Malay language and English as the second widely used language in this country. Therefore, the present study was conducted with two objectives namely: 1) To investigate the attitude of non-Malay UNITEN students towards Malay and English language, and 2) To examine the perception of non-Malay UNITEN students towards using Malay and English language with Malay people. The findings showed that most of the respondents, 55 (M= 2.37, SD= 1.079) surprisingly assigned â€œagreedâ€ to item 2 (â€œI like using Malay language as a second languageâ€) despite admitting they did not possess good Malay language skills for their responses to item 1. This shows that the respondents seem to have mixed feelings regarding the issues of using Malay language in relation to certain aspects and this is also true for English.Â Â Â